The Influence of Word of Mouth, Advertising, Discounts, and Perceived Ease of Use on Purchase Decisions through Online Food Platforms - Afnan Hanif Nafaro; Alfalisyado Alfalisyado; Wida Purwidianti; Luthfi Zamakhsyari (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze the effect of word of mouth, advertising, discounts, and perceived ease of use on purchasing decisions through the GoFood service. The subjects of this study are GoFood users, with a total of 112 respondents, and the sample size is determined using Roscoe's theory. The sampling technique used is non-probability sampling with purposive sampling. The data analysis used in this study includes Tests instrument, Classical Assumption Tests, Multiple Linear Regression Tests, and Model Fit Tests. The results of this study indicate that Word of mouth has a positive and significant effect on purchasing decisions, Advertising has a positive and significant effect on purchasing decisions, Discounts have a negative and significant effect on purchasing decisions, and Perceived ease of use does not affect purchasing decisions.